2020
DOI: 10.1080/1461670x.2020.1727355
|View full text |Cite
|
Sign up to set email alerts
|

Victims and Voices: Journalistic Sourcing Practices and the Use of Private Citizens in Online Healthcare-system News

Abstract: The opportunity for non-elite actors to share their opinions and experiences is often cited as a key democratic element of the media, developing in recent years alongside a rethinking of the audience as active contributors. Yet, given many of the temporal and resource-related newsroom pressures, the reliance on information subsidies and official or elite voices remains pervasive. This study focuses on coverage of healthcare and health policy, drawing on 14 weeks of news reports (n=896) from five Irish websites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
(50 reference statements)
2
11
0
Order By: Relevance
“…Journalists employ episodic frames to illustrate wider issues in ways that humanize their topic, which is especially common in commercially oriented outlets (De Swert and Kuypers 2020). Ordinary citizens have accordingly become increasingly prominent in news coverage (De Keyser and Raeymaeckers 2012; Kleemans et al 2017) for a variety of reasons: the urge for less costly content (Wheatley 2020); the commercial need to produce appealing stories (Skovsgaard and Hopmann 2020); and a movement toward public journalism (Ahva 2013). From a normative perspective, this increase in episodic framing is positive (Althaus 2012) when considering participatory-oriented theories of democracy: It sparks a more diverse “market place of ideas” and allows citizens to represent themselves by breaking through the hegemony of elite sources.…”
mentioning
confidence: 99%
“…Journalists employ episodic frames to illustrate wider issues in ways that humanize their topic, which is especially common in commercially oriented outlets (De Swert and Kuypers 2020). Ordinary citizens have accordingly become increasingly prominent in news coverage (De Keyser and Raeymaeckers 2012; Kleemans et al 2017) for a variety of reasons: the urge for less costly content (Wheatley 2020); the commercial need to produce appealing stories (Skovsgaard and Hopmann 2020); and a movement toward public journalism (Ahva 2013). From a normative perspective, this increase in episodic framing is positive (Althaus 2012) when considering participatory-oriented theories of democracy: It sparks a more diverse “market place of ideas” and allows citizens to represent themselves by breaking through the hegemony of elite sources.…”
mentioning
confidence: 99%
“…Despite a predominance of official sources, other social players may try to influence the press, such as the case of citizens as sources, even if this struggle for predominance is mostly unbalanced [ 43 ]. Democratic societies seem to view favourably the use of general public as a source by the media [ 44 ]. They include in that group patient associations’ representatives who mobilise themselves to gain visibility in the media [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated the influence of health-related state agencies, politicians, and trade unions in gaining media attention via PR material which was typically repurposed without much amendments from the journalists. Elsewhere, we learnt that ordinary/private citizens were often included in the news and becoming salient voices, but often only because of their contributions to talk radio shows in which users call in and make comments, which then get repurposed by journalists in other rival outlets (Wheatley, 2020b). Regarding temporality and the rhythms of online publishing cycles, this methodological approach also allowed us to see that among legacy newspaper brand outlets, there was still often a print-first mentality still present; more original journalism work was often held for the print edition first, and more superficial reporting (often based on press releases and repackaged material from other media) was typically used to populate the outlets' websites during the day, helping to fill the perceived open-ended news gap (Wheatley & O'Sullivan, 2017).…”
Section: Issn: 2659-9538mentioning
confidence: 99%
“…Therefore, linking practice to published content requires a fresh approach to content analysis, one which moves beyond a one-dimensional analysis of the text which has limitations when trying to understand practice, discussed further below. For that reason, novel methods are needed to develop the link between daily actions and output: the approach outlined here is the basis of studies published elsewhere (Wheatley 2017(Wheatley , 2020a(Wheatley , 2020b, and this space provides an opportunity to focus more deeply on the steps and motivation of this approach. To strengthen the content analysis work into online journalism specifically, Steensen has suggested that it should be combined with more qualitative approaches to the analysis of texts which can help to understand the field's complexity (2011, p. 322).…”
Section: Introductionmentioning
confidence: 99%